Pelatihan Cara Penyimpanan Dan Distribusi Vaksin Yang Baik Kepada Pegawai Gudang Farmasi dinas Kesehatan Kota Bengkulu - Wirahmi, Nori; Versita, Riana; Ikhsan, Ikhsan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The World Health Organization (WHO) has established Covid-19 (Coronavirus Disease 2019) as a public health emergency of international concern (Public Health International Concern) which carries a risk of transmission between countries. Cases of Covid-19 have been identified since February 26 2020 in Indonesia. The spread of the SARS-CoV-2 virus as the cause of Covid-19 disease is increasingly becoming massive throughout the world, including in Indonesia, it has even entered Bengkulu Province. The ferocity of this virus in attacking the respiratory tract has caused thousands of medical and paramedical personnel and even civil society to suffer and die. The method of this community service activity is the method of providing training on vaccine CDOB materials and practices and managing the vaccine cold chain. Then monitoring of the vaccine distribution process was carried out after training for officers. Finally, an evaluation was carried out with a pretest and filling in the vaccine distribution report by the officer. This activity was carried out with 3 students. The next activity is that on October 30, 2021 an online evaluation will be carried out by filling out a Google form to see the level of understanding of the Bengkulu City Health Service Pharmacy Warehouse employees regarding Proper Vaccine Storage and Distribution. The evaluation results obtained showed a good score where all participants received maximum scores. The Community Service Activity on Training on Proper Storage and Distribution of Vaccines to Employees of the Bengkulu City Health Service Pharmacy Warehouse has been carried out well and received a very good response from the participants. It is recommended to conduct other trainings that can improve health, both in the health environment and to the wider community.Keyword : Vaccine, Covid-19, Department of Health